Germline variants at SOHLH2 influence multiple myeloma risk - Duran-Lozano, Laura; Thorleifsson, Gudmar; Lopez de Lapuente Portilla, Aitzkoa; Niroula, Abhishek; Went, Molly; Thodberg, Malte; Pertesi, Maroulio; Ajore, Ram; Cafaro, Caterina; Olason, Pall I.; Stefansdottir, Lilja; Bragi Walters, G.; et al. (Blood cancer journal, 2021)
Multiple myeloma (MM) is caused by the uncontrolled, clonal expansion of plasma cells. While there is epidemiological evidence for inherited susceptibility, the molecular basis remains incompletely understood. We report a genome-wide association study totalling 5,320 cases and 422,289 controls from four Nordic populations, and find a novel MM risk variant at SOHLH2 at 13q13.3 (risk allele frequency = 3.5%; odds ratio = 1.38; P = 2.2 × 10−14). This gene encodes a transcription factor involved in gametogenesis that is normally only weakly expressed in plasma cells. The association is represented by 14 variants in linkage disequilibrium. Among these, rs75712673 maps to a genomic region with open chromatin in plasma cells, and upregulates SOHLH2 in this cell type. Moreover, rs75712673 influences transcriptional activity in luciferase assays, and shows a chromatin looping interaction with the SOHLH2 promoter. Our work provides novel insight into MM susceptibility.
Gesehen am 28.05.2021